School Management Strategies for Developing Characteristics of Thai Children in The ASEAN Community - Charoenphao, Parujee; Visetsiri, Pongsin; Usaho, Chayapim (Scholar: Human Sciences, 2016)
The objectives of this research were 1) to study the current and desirable states of school management for developing characteristics of Thai children in the ASEAN community. 2) to analyze strengths, weaknesses, opportunities and threats of school management for developing characteristics of Thai children in the ASEAN community and 3) to develop school management strategies for developing characteristics of Thai children in the ASEAN community. The study was mixed-method research. The samples were 183 state-maintained kindergartens. The informants include 131 school administrators and 167 teachers responsible for the ASEAN projects, 298 people in total. The instruments used in this study were a questionnaire and an evaluation form to determine the feasibility and suitability of strategies. The data were analyzed by frequency, percentage, average, standard deviation, PNIModified and content analysis. The research results showed the following: 1) The current state of the management for developing characteristics of Thai children in the ASEAN community was overall at a high level ( = 3.695).When considering each aspect, the social aspect was at the highest average (x= 3.843). The desirable state of management for developing characteristics of Thai children in the ASEAN community was overall at a high level ( = 4.677).When considering each aspect, the social aspect was at the highest average (x= 4.754). 2) The strength of management for developing characteristics of Thai children in the ASEAN community was the social aspect. The weaknesses were skills, environment and knowledge respectively. The government policies and technology were considered as the opportunities of management for developing characteristics of Thai children in the ASEAN community. The economy and society were considered as the threats of management for developing characteristics of Thai children in the ASEAN community. 3) Four management strategies were developed including (i) To reform school management for promoting Thai children’s skills of the ASEAN community; (ii) To reform school management for promoting Thai children’s environment of the ASEAN community; (iii) To reform school management for promoting Thai children’s knowledge of the ASEAN community; and (iv) To reform school management for promoting Thai children’s society of the ASEAN community.